2016
DOI: 10.1071/sr15106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of greenhouse soil bio-disinfection on soil nitrate content and tomato fruit yield and quality

Abstract: Intensive horticultural practices in the greenhouse can cause proliferation of soil phytopathogenic organisms and pollution of groundwater from nitrate leaching. Among the different soil disinfection techniques, bio-disinfection through the addition of organic amendments (OA), with subsequent solarisation (biosolarisation) or without (biofumigation), is an efficient and economically viable alternative for the control of soil pathogens. This greenhouse experiment was conducted to initiate the process of convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 31 publications
5
23
0
Order By: Relevance
“…It should be noted that the fruits from plants treated with fertigation, in the first year, had higher size and weight than fruits of the others treatments, but not in the second year. Similar values to those values reported by other authors: Marín-Guirao et al [11] obtained values for acidity, ºBrix and color similar to this study. However, Mauromicale et al [16] reported that parameters, such as firmness, color and soluble solids content (ºBrix), were increased proportionally to the increase in organic matter in the treatments used, contrasting with the results of this study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It should be noted that the fruits from plants treated with fertigation, in the first year, had higher size and weight than fruits of the others treatments, but not in the second year. Similar values to those values reported by other authors: Marín-Guirao et al [11] obtained values for acidity, ºBrix and color similar to this study. However, Mauromicale et al [16] reported that parameters, such as firmness, color and soluble solids content (ºBrix), were increased proportionally to the increase in organic matter in the treatments used, contrasting with the results of this study.…”
Section: Discussionsupporting
confidence: 93%
“…Supplementation with the pellets resulted in an improvement in yield, but not significantly. These findings are partly consistent with those of López-Aranda et al [46], Pane et al [47] and Marín-Guirao et al [11], who did not report any benefit with Biofence® application. Pane et al [47] suggest that the application of brassica carinata flour, with or without solarization, could have a protective effect on some microbial groups that benefit soil activity and establishment of the crop.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…as organic amendment showed NO 3 ‐ accumulation. However, this study also showed that SBS has lower NO 3 ‐ contamination potential than other practices, as a consequence of the lower irrigation of the soil during the process …”
Section: Discussionmentioning
confidence: 99%
“…In particular, in 2014 Almería produced approximately 1,900,000 tons of non-dehydrated residues from horticultural crops [8,9]. Furthermore, organic matter resources, such as green manure, mulching, animal manure, and crop waste, are frequently added to the soil through biofumigation and biosolarization to prepare the soil for the next crop [10,11].…”
Section: Introductionmentioning
confidence: 99%